The effect of personalised adjustments to computer workstations on the efficiency and physical comfort of computer operators - James, Genevieve (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2005)
The present study sought to investigate the effects of a Standard workstation, designed for "average" users, on an anthropometrically diverse sample of computer operators, and to assess whether physical and perceptual responses, as well as performance efficiency were dependent on stature. Further investigation assessed the influence of personalised adjustments to the Standard workstation, based on the anthropometric characteristics of the subjects, as well as the introduction of a custom-designed 'floating' wrist support, on subject responses. All subjects (n=30) were tested in each of the three workstations: Standard, Personalised and Wrist Support. For analysis of responses in the Standard workstation, subjects were divided into three groups depending on their stature: Short (<1650mm), Medium (1650mm to 1800mm), Tall (>1800mm). The musculoskeletal responses indicated that Tall subjects were forced to adopt the most awkward general body postures as a result of the low computer screen. However, the low screen allowed for the Short subjects to adopt the most natural general body postures, although levels of muscular activity in the upper trapezius suggest that the muscular load imposed on both Short and Tall subjects was significantly greater than that imposed on the Medium subjects. In addition, the Medium subjects' perceptions of the Standard workstation dimensions support the fact that this workstation was better suited to users with "average" morphologies. The responses elicited in the Personalised and Wrist Support workstations were improved significantly when compared to the Standard workstation. Joint angles were more natural, upper trapezius EMG was reduced, standard of performance improved and perceptual responses indicated a diminished incidence of body and visual discomfort, as well as greater perceived satisfaction with these workstation dimensions. The improved physical responses suggest a decrease in the risk of developing cumulative trauma disorders. Although subjects were unaccustomed to the wrist support device, this workstation demonstrated a further reduction in the range of wrist angles, as well as a general positive attitude towards the concept.
Keywords: Human engineering; Engineering design; Work environment; Microcomputer workstations -- Health aspects; Occupational diseases -- Prevention